2016
DOI: 10.1109/lcomm.2016.2580503
|View full text |Cite
|
Sign up to set email alerts
|

Uncoded Space-Time Labeling Diversity

Abstract: In this letter, we apply labeling diversity to a spacetime block coded system, which does not require channel coding or bit interleaving. The proposed system is investigated for both Rayleigh frequency-flat fast and quasi-static fading channels. The theoretical average bit error probability (ABEP) of the system is formulated using the union bound approach. A possible optimization criterion for the design of the mappers for both Mary quadrature amplitude modulation (MQAM) and M-ary phase shift keying (MPSK) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
225
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 46 publications
(228 citation statements)
references
References 14 publications
3
225
0
Order By: Relevance
“…4 Following the analysis approach by Xu et al, 4 we also assume that at high SNR, only one pair of super symbols is detected with errors, while the other pair of super symbols is detected correctly. The error performance analysis of STLD was based on that at high SNR, only one symbol is detected with errors, while the other one is detected correctly.…”
Section: Error Performance Analysis Of Ci-gc-mqammentioning
confidence: 99%
“…4 Following the analysis approach by Xu et al, 4 we also assume that at high SNR, only one pair of super symbols is detected with errors, while the other pair of super symbols is detected correctly. The error performance analysis of STLD was based on that at high SNR, only one symbol is detected with errors, while the other one is detected correctly.…”
Section: Error Performance Analysis Of Ci-gc-mqammentioning
confidence: 99%
“…Although the BER performance of SM was significantly enhanced by the application of STBC, further improvement via the application of labeling diversity can be realised. As demonstrated in Xu et al, the BER performance of the conventional STBC system was significantly improved via the use of labeling diversity. Hence, this motivates for the application of labeling diversity to STBC‐SM, hereinafter referred to as STBC‐SM‐LD, which, to the best of the authors' knowledge, has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 95%
“…A 2 × N r STLD system is shown in Figure , where N r is the number of receive antennas. The STLD system is a modification of the conventional 2 × N r STBC system, where the fundamental idea is to transmit a mapped symbol pair in the second time slot instead of the complex conjugates . The STLD system generates the 2 × 2 STBC based on 2 mappers: ω1M and ω2M0.25em as in Xu et al Figures and illustrate the Gray‐coded labeling map ω116 and the optimised labeling map ω216 for 16‐QAM, while Figures and illustrate the Gray‐coded labeling map ω164 and the optimised labeling map ω264 for 64‐QAM .…”
Section: System Models and Backgroundmentioning
confidence: 99%
See 2 more Smart Citations